Cybersquatting as a Type of Trademark Infringement and its Impact on Fair Competition - Kalemaj, Endi; Çela, Ervis; Qoku, Maksim (Law, State and Telecommunications Review, 2026)
[Purpose] The aim of the study was to critically analyse cybersquatting as a legal and economic anomaly of the digital market. [Methodology/approach/design] The methodology of the work was based on a combination of the comparative-legal method, detailed analysis of legal acts, international policies and the generalisation of key precedents of judicial and arbitration practice [Findings] During the study it was established that cybersquatting encompassed various unfair practices, including typosquatting, name-jacking and abuses by registrars. Key protection instruments were analysed: the administrative Uniform Domain-Name Dispute-Resolution Policy and the judicial American Anticybersquatting Consumer Protection Act. In particular, the American approach was based on proving “bad faith intent” under nine judicial factors, whereas the international administrative procedure required the complainant to prove three cumulative criteria to satisfy the complaint. As a result of the comparative analysis of the legal models of the United States of America, Germany, France and Albania, four distinct approaches to regulation were identified: judicial with financial sanctions, hybrid with domain blocking, hybrid with alternative dispute resolution and a model of direct implementation of international standards. It was proved that this phenomenon created artificial barriers to market entry, especially for small and medium-sized businesses, undermined trust in e-commerce, as well as caused significant direct (costs of domain redemption, legal support) and indirect (loss of traffic, reputational damage) economic losses. [Practical implications] The practical significance of the work lay in the fact that its results could be used to improve national legislation in the field of intellectual property, to develop more effective corporate strategies for the protection of digital assets, as well as serve as methodological material for the training of lawyers and arbitrators specialising in the resolution of domain disputes. [Originality/value] The study’s scholarly contribution lies in its systematic comparative analysis that identifies four distinct regulatory models across jurisdictions (the strict judicial model of the USA, Germany’s hybrid administrative-blocking approach, France’s specialized ADR system, and Albania’s direct implementation of international standards), while demonstrating how cybersquatting functions as both a legal anomaly exploiting regulatory gaps and an economic distortion that disproportionately affects small and medium-sized enterprises through the creation of artificial market barriers and "cyber-inequality."